2016
DOI: 10.1002/2015gl066612
|View full text |Cite
|
Sign up to set email alerts
|

High basal melting forming a channel at the grounding line of Ross Ice Shelf, Antarctica

Abstract: Antarctica's ice shelves are thinning at an increasing rate, affecting their buttressing ability. Channels in the ice shelf base unevenly distribute melting, and their evolution provides insight into changing subglacial and oceanic conditions. Here we used phase‐sensitive radar measurements to estimate basal melt rates in a channel beneath the currently stable Ross Ice Shelf. Melt rates of 22.2 ± 0.2 m a−1 (>2500% the overall background rate) were observed 1.7 km seaward of Mercer/Whillans Ice Stream grounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 33 publications
(50 reference statements)
7
121
0
Order By: Relevance
“…A similar mechanism is proposed by Marsh et al (2016) for the WIS subglacial channel outflow area. If this mechanism is operating at the KIS, it is probable that the strong basal melting by the outflow of its subglacial water system could create a similar channel there.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A similar mechanism is proposed by Marsh et al (2016) for the WIS subglacial channel outflow area. If this mechanism is operating at the KIS, it is probable that the strong basal melting by the outflow of its subglacial water system could create a similar channel there.…”
Section: Discussionmentioning
confidence: 89%
“…Comparison of our results to those of Siegfried et al (2016) only confirm that the subglacial water system in the WIS is more active than the KIS trunk subglacial lake system, since volume changes in the WIS system are 3-10 times as large as in the KIS trunk system. Marsh et al (2016) reported extremely large melt rates (22.2±0.2 m yr −1 ) at the site of inferred subglacial water discharge at the Whillans/Mercer Ice Stream grounding line. Strong basal melting is also inferred from the elevation loss rate (up to ∼ 1.5 m yr −1 ) in the narrow channel near the grounding line of the KIS, but the basal melt rate cannot be exactly projected from the observed elevation lowering due to the possibility of bridging stresses across the narrow channel feature.…”
Section: Discussionmentioning
confidence: 99%
“…the difference between refreezing and melting. Point measurements with phase-sensitive radars (Marsh et al, 2016;Nicholls et al, 2015), global navigation satellite system (GNSS) receivers (Shean et al, 2017), observations from underwater vehicles (Dutrieux et al, 2014) and analysis from high-resolution satellites (Dutrieux et al, 2013;Wilson et al, 2017) have shown that BMB varies spatially on sub-kilometre scales. Ice shelf channels are one expression of localized basal melting (Stanton et al, 2013;Marsh et al, 2016) which, after hydrostatic adjustment, form curvilinear depressions visible at the ice shelf surface (Fig.…”
Section: S Berger Et Al: Spatial Variability Of Ice Shelf Basal Masmentioning
confidence: 99%
“…Processing and acquisition schemes are as outlined previously (Nicholls et al, 2015;Marsh et al, 2016). The radar antennas were positioned at 22 sites.…”
Section: On-site Geophysical Measurementsmentioning
confidence: 99%
“…Therefore, monitoring the stability of the ice shelves is an integral part of the study of AIS mass changes and the associated sea level rise. As some smaller sized ice shelves in the lower latitude and warmer Antarctic Peninsula region, such as the Larsen B ice shelf, experienced collapses (Scambos 5 et al, 2004;Braun et al, 2009), changes of the two largest ice shelves, Ross Ice Shelf (RIS) and RonneFilchner Ice Shelf (RFIS), have also been intensely studied (Hulbe et al, 1998;Larour et al, 2004;Joughin and MacAyeal, 2005;Makinson et al, 2011;Scheuchl et al, 2012;Marsh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%